2001
DOI: 10.1046/j.1365-2265.2001.1139cn2155.x
|View full text |Cite
|
Sign up to set email alerts
|

T lymphopaenia in relation to body mass index and TNF‐α in human obesity: adequate weight reduction can be corrective

Abstract: Our results suggest that subsets of T cell populations and their function may be reduced in human obesity, and that this may be related, at least in part, to the elevated TNF-alpha production. Furthermore, this T cell dysfunction can be recovered by adequate weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 38 publications
1
43
0
3
Order By: Relevance
“…Obese patients after a moderate energy restriction have a lower mitogen-stimulated proliferation response and decreased monocyte oxidative burst as well as NK cell counts, but not T-and B-cell counts (Nieman et al, 1996). While total lymphocyte numbers did not change after a weight reduction program, the response of T-lymphocytes to different mitogens was increased as well as B-lymphocyte blastogenesis at the end of the dietary restriction period (Tanaka et al, 2001). During the slimming period, fasting blood glucose and serum triglyceride concentrations were slightly reduced.…”
Section: Obese Individuals and Immune Functionmentioning
confidence: 89%
“…Obese patients after a moderate energy restriction have a lower mitogen-stimulated proliferation response and decreased monocyte oxidative burst as well as NK cell counts, but not T-and B-cell counts (Nieman et al, 1996). While total lymphocyte numbers did not change after a weight reduction program, the response of T-lymphocytes to different mitogens was increased as well as B-lymphocyte blastogenesis at the end of the dietary restriction period (Tanaka et al, 2001). During the slimming period, fasting blood glucose and serum triglyceride concentrations were slightly reduced.…”
Section: Obese Individuals and Immune Functionmentioning
confidence: 89%
“…Excess weight contributes to several health related complications which may include diabetes, cancers, kidney disease and hypertension [11]. It is indicated that obesity resulted in decreased immune counts and functions [22].…”
Section: Discussionmentioning
confidence: 99%
“…The power of NLR as an inflammatory factor stems from both a reduction in the lymphocyte count and an increase in the neutrophil count. Tanaka et al (30) showed that T lymphocytes were reduced in obese people and that lymphopenia appeared to be related to inflammation through TNFa. Neutrophils are the first immune cells to respond to inflammation and can exacerbate the chronic inflammatory state by helping recruit macrophages and by interacting with antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%